Sistem Informasi Penyedia Lowongan Kerja Berbasis Web - Masnur, Masnur; Difla, Difla Iklila (Jurnal Sintaks Logika, 2021)
In searching for job vacancy information, applicants usually still use conventional methods, namely by visiting companies to view job vacancy notice boards, conducting searches in print media such as newspapers, magazines, brochures or person-to-person information. Likewise with companies that want to open job vacancies.One way to update information faster is by designing a web-based job information system application. In this web-based job provider information system built there will be search information according to the criteria. In conducting this research, researchers used an experimental method where the process begins with developing an existing system. The system implementation and system maintenance uses the PHP programming language for this project.The results achieved from this application using the Black Box method, which is obtained that the application runs well according to the design that has been made.